2021
DOI: 10.3390/math9192391
|View full text |Cite
|
Sign up to set email alerts
|

Proposing an Intelligent Dual-Energy Radiation-Based System for Metering Scale Layer Thickness in Oil Pipelines Containing an Annular Regime of Three-Phase Flow

Abstract: Deposition of scale layers inside pipelines leads to many problems, e.g., reducing the internal diameter of pipelines, damage to drilling equipment because of corrosion, increasing energy consumption because of decreased efficiency of equipment, and shortened life, etc., in the petroleum industry. Gamma attenuation could be implemented as a non-invasive approach suitable for determining the mineral scale layer. In this paper, an intelligent system for metering the scale layer thickness independently of each ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 77 publications
(69 reference statements)
0
12
0
Order By: Relevance
“…As it can be used to optimize products and reduce costs. A large and growing body of literature has investigated the use of AI in several industries [28][29][30][31]. Therefore, the use of AI can be a good alternative to be used for gaining more information from capacitance-based sensors [32].…”
Section: Resultsmentioning
confidence: 99%
“…As it can be used to optimize products and reduce costs. A large and growing body of literature has investigated the use of AI in several industries [28][29][30][31]. Therefore, the use of AI can be a good alternative to be used for gaining more information from capacitance-based sensors [32].…”
Section: Resultsmentioning
confidence: 99%
“…They also used a support vector machine (SVM) to compute solubility product data of barite in brines. Other studies have reported simulations of two-phase [6][7][8] and three-phase [9][10][11] flows at varying volume percentages and flow regimes. Others focused on ascertaining the volume percentage and flow regime using various neural networks, such as MLP [12,13], RBF [14,15], adaptive neuro-fuzzy inference system [16], Jaya algorithm [17], and GMDH neural network [18].…”
Section: Introductionmentioning
confidence: 99%
“…Nondestructive testing (NDT) can supply pipe's basic data, and it plays an important role in developing intelligent pipelines. e ultrasonic in-line inspection technology is an e cient way to detect cracks [2] which appear and grow in pipes exposed to various environmental media [3] and loading conditions [4]. Several types of ultrasonic inspection tools are in progress of developing.…”
Section: Introductionmentioning
confidence: 99%